GUGATAN PEREMPUAN ATAS MAKNA PERKAWINAN STUDI TENTANG CERAI-GUGAT DI KOTA PEKALONGAN - Kustini Kustini; Nur Rofiah (Harmoni, 2015)
Divorce is seen as the most hated halal based on Allah viewpoint stated in Hadits that Muslims must build marriage system and tradition to achieve harmonious and happy family, so the divorce can be prevented. In fact, the divorce phenomenon happens in some areas in Indonesia, particularly wifeinitiated divorce. This research focuses on three aspects. The first one is the reason of wives to propose divorce. The second is its effects and the last is social structure response towards divorce phenomenon. This study applies qualitative approach and the data collection techniques consist of interview, document analysis, and observation. The result of study shows that the loss of marriage meaning is caused by the divorce. Divorce also contributes negative impact for family life and children. However, in some certain time it can give positive impact for women because they have obvious status and do not burden to do their duty as wives.